Extensively Invasive Gallbladder Cancer from Intracholecystic Papillary Neoplasm Treated with Pylorus-Preserving Pancreaticoduodenectomy and Extended Cholecystectomy: A Case Report and Literature Review - Hideki Kumagai; Akira Umemura; Hiroyuki Nitta; Hirokatsu Katagiri; Masao Nishiya; Noriyuki Uesugi; Tamotsu Sugai; Akira Sasaki (Case Reports in Surgery)
Background. Intracholecystic papillary neoplasm (ICPN) is a rare tumor first classified by the World Health Organization in 2010. ICPN is a counterpart of the intraductal papillary mucinous neoplasm of the pancreas and intraductal papillary neoplasm of the bile duct. Previous reports on ICPN are limited; thus, the diagnosis, surgical intervention, and prognosis are controversial. Here, we report an extensively invasive gallbladder cancer arising in ICPN treated with pylorus-preserving pancreaticoduodenectomy (PPPD) and extended cholecystectomy. Case Presentation. A 75-year-old man presented to another hospital with jaundice for 1 month. Laboratory findings showed elevated total bilirubin, 10.6 mg/dL and carbohydrate antigen 19-9, 54.8 U/mL. Computed tomography showed a well-enhanced tumor located in the distal bile duct and dilated hepatic bile duct. The gallbladder wall was thickened and homogeneously enhanced. Endoscopic retrograde cholangiopancreatography revealed a filling defect in the distal common bile duct, and intraductal ultrasonography showed a papillary tumor in the common bile duct, indicating tumor invasion of the bile duct subserosa. Subsequent bile duct brush cytology revealed adenocarcinoma. The patient was referred to our hospital for surgical treatment and underwent an open PPPD. Intraoperative findings showed a thickened and indurated gallbladder wall, suggesting concurrent gallbladder cancer; thus, the patient subsequently underwent PPPD and extended cholecystectomy. Histopathological findings confirmed gallbladder carcinoma originating from ICPN, which extensively invaded the liver, common bile duct, and pancreas. The patient started adjuvant chemotherapy (tegafur/gimeracil/oteracil) 1 month after surgery and had no recurrence at follow-up after 1 year. Conclusions. Accurate preoperative diagnosis of ICPN, including the extent of tumor invasion is challenging. To ensure complete curability, the development of an optimal surgical strategy considering preoperative examinations and intraoperative findings is essential.